Patient preferences regarding chemotherapy in metastatic breast cancer: a conjoint analysis for common taxanes - Spaich, Saskia; Kinder, Johanna; Hetjens, Svetlana; Fuxius, Stefan; Gerhardt, Axel; Sütterlin, Marc (Frontiers in oncology, 2018)
Background: Purpose of this investigation was to explore patient perception regarding the importance of efficacy, toxicity and regimen of taxane-based chemotherapy (CHT) for metastatic breast cancer (MBC). Methods: This dual-center study analysed data of 100 women diagnosed with MBC, who were asked for their preferences regarding chemotherapy by means of conjoint analysis. Included attributes were progression free survival (PFS), application form, time and frequency, need of premedication, risk of alopecia, fatigue, febrile neutropenia and neuropathy. Furthermore, participants completed a questionnaire about their personal and medical history. Regression analyses were performed to identify factors that influence patient preference in terms of specific treatment choice. Results: Of 8 attributes, severe neutropenia was top priority for the majority of patients, followed by alopecia, neuropathy and PFS. When combining these patient preferences and the results of the questionnaire, patients´ age as well as relationship status had significant impact on the importance of PFS. Moreover, longer travel time to the treatment centre was significantly associated with preferences regarding PFS. Ranking by combination of respective part-worth values demonstrated nab-paclitaxel to be favoured over paclitaxel and docetaxel. Conclusion: Side effects of CHT and PFS prove to be critical factors for patients affecting choice of treatment in MBC with severe neutropenia being top priority, followed by alopecia, neuropathy and PFS. Age, commute time and relationship status were identified as significant determinants of patient preference. Total utility calculation by combination of part-worth values ranked nab-paclitaxel as the most preferable taxane.